Mental health nursing and the negotiated order: A critical analysis of psychotherapy discourses in Québec (Canada) - Pariseau-Legault, Pierre; Ayala, Ricardo A.; Labrecque-Lebeau, Lisandre; Vallée-Ouimet, Sandrine; Bujold, Audrey; Gervais, Christine (Aporia, 2025)
Access to mental health care remains a pressing global issue. In response, policymakers have devised strategies that span from self-care to psychotherapy, hoping to ease the strain. However, reforms over the past two decades have significantly restricted access to psychotherapy, limiting the number of professionals, such as nurses, allowed to practise under stringent conditions. This article examines the effects of Quebec’s public policies on the practice of psychotherapy and mental health interventions. A critical discourse analysis, grounded in Strauss’s theory of negotiated order, was conducted on 48 policy documents and public discourses. The findings reveal that mental health interventions have become disconnected from their therapeutic essence, reduced instead to technical tasks. This shift perpetuates a hierarchical professional landscape, subordinating these practices despite their reliance on the relational dynamics that define effective mental health care. For the nursing profession, the implications are profound. The profession’s contribution to providing timely access to community-based mental health services is being overlooked, stymied by outdated perceptions and policy restrictions.